Imaging Protocols in Clinical Studies in Advanced Age-Related Macular Degeneration: Recommendations from Classification of Atrophy Consensus Meetings - Holz, Frank G; Sadda, SriniVas R; Staurenghi, Giovanni; Lindner, Moritz; Bird, Alan C; Blodi, Barbara A; Bottoni, Ferdinando; Chakravarthy, Usha; Chew, Emily Y; Csaky, Karl; Curcio, Christine A; Danis, Ron; et al. (Ophthalmology (Rochester, Minn.), 2017)
To summarize the results of 2 consensus meetings (Classification of Atrophy Meeting [CAM]) on conventional and advanced imaging modalities used to detect and quantify atrophy due to late-stage non-neovascular and neovascular age-related macular degeneration (AMD) and to provide recommendations on the use of these modalities in natural history studies and interventional clinical trials. Systematic debate on the relevance of distinct imaging modalities held in 2 consensus meetings. A panel of retina specialists. During the CAM, a consortium of international experts evaluated the advantages and disadvantages of various imaging modalities on the basis of the collective analysis of a large series of clinical cases. A systematic discussion on the role of each modality in future studies in non-neovascular and neovascular AMD was held. Advantages and disadvantages of current retinal imaging technologies and recommendations for their use in advanced AMD trials. Imaging protocols to detect, quantify, and monitor progression of atrophy should include color fundus photography (CFP), confocal fundus autofluorescence (FAF), confocal near-infrared reflectance (NIR), and high-resolution optical coherence tomography volume scans. These images should be acquired at regular intervals throughout the study. In studies of non-neovascular AMD (without evident signs of active or regressed neovascularization [NV] at baseline), CFP may be sufficient at baseline and end-of-study visit. Fluorescein angiography (FA) may become necessary to evaluate for NV at any visit during the study. Indocyanine-green angiography (ICG-A) may be considered at baseline under certain conditions. For studies in patients with neovascular AMD, increased need for visualization of the vasculature must be taken into account. Accordingly, these studies should include FA (recommended at baseline and selected follow-up visits) and ICG-A under certain conditions. A multimodal imaging approach is recommended in clinical studies for the optimal detection and measurement of atrophy and its associated features. Specific validation studies will be necessary to determine the best combination of imaging modalities, and these recommendations will need to be updated as new imaging technologies become available in the future.